PENGARUH KONSUMSI PISANG AMBON TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - Alifariki, La Ode (NHM PRESS, 2023)
Hypertension is one of the most common cardiovascular diseases and is the number 1 killer, so it needs treatment and prevention. Treatment of patients with natural ingredients can reduce family expenses and reduce the impact or negative effects of chemical treatment. The final results were collected as many as 8 articles that met the inclusion criteria. Various research results in this study provide a similar picture, namely that there is a decrease in systolic and diastolic blood pressure after administering ambon banana.